2015
DOI: 10.1152/ajpheart.00787.2014
|View full text |Cite
|
Sign up to set email alerts
|

Splenic autonomic denervation increases inflammatory status but does not aggravate atherosclerotic lesion development

Abstract: The brain plays a prominent role in the regulation of inflammation. Immune cells are under control of the so-called cholinergic anti-inflammatory reflex, mainly acting via autonomic innervation of the spleen. Activation of this reflex inhibits the secretion of proinflammatory cytokines and may reduce the development of atherosclerosis. Therefore, the aim of this study was to evaluate the effects of selective parasympathetic (Px) and sympathetic (Sx) denervation of the spleen on inflammatory status and atherosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 27 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…At the heart of this debate is the apparent lack of vagal innervation to the spleen. While some studies have reported evidence of vagal innervation at the splenic poles in rodents(38), this remains controversial, and most current reports favor a mechanism in which efferent vagal signals are transmitted to the spleen via sympathetic nerves (this hypothesis however, has been also refuted(40)), which enter along the vessels of the splenic plexus, and/or via non neuronal acetylcholine signaling initiated by circulating T-cells which receive vagal input outside of the splenic parenchyma (41, 42). Both of these pathways are thought to result in activation of α-7-containing nicotinic receptors on splenic macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…At the heart of this debate is the apparent lack of vagal innervation to the spleen. While some studies have reported evidence of vagal innervation at the splenic poles in rodents(38), this remains controversial, and most current reports favor a mechanism in which efferent vagal signals are transmitted to the spleen via sympathetic nerves (this hypothesis however, has been also refuted(40)), which enter along the vessels of the splenic plexus, and/or via non neuronal acetylcholine signaling initiated by circulating T-cells which receive vagal input outside of the splenic parenchyma (41, 42). Both of these pathways are thought to result in activation of α-7-containing nicotinic receptors on splenic macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, AST and ALT activities are widely used as key biochemical indicators to indicate the severity of liver injury . CP stimulation can significantly increase the serum transaminase level, and GAA intervention can improve the serum transaminase level.…”
Section: Discussionmentioning
confidence: 99%
“…As a part of the mononuclear phagocyte system, the spleen can be regarded as a large lymph node, because its absence usually leads to a predisposition to infections [ 20 ]. Meanwhile, it has been reported in mice that half of the body's monocytes are reserved within the red pulp of spleen [ 21 ]. When tissue damage happened, these monocytes would move to injured tissue transforming into dendritic cells and macrophages to facilitate the treatment of tissue.…”
Section: Discussionmentioning
confidence: 99%